Understanding by Design (UbD): An Effective Way to Design Elementary School Science Learning for the Competencies of Teacher Professional Education Students - Woro Sri Hastuti; Febrina Siska Widyaningtyas; Unik Ambar Wati; Sandy Abdi Kusumah (STAI Hubbulwathan Duri, 2025)
Many pre-service teachers in Teacher Professional Education (PPG) programs lack the competence to develop effective teaching materials aligned with curriculum goals. Understanding by Design (UbD) offers a structured approach to support this development through backward design. This study employed a quantitative research design using purposive sampling to select 116 PPG students as respondents. Data were collected via an online questionnaire distributed through Google Forms. The collected data were analyzed using descriptive statistical methods. Findings reveal that UbD effectively supports the development of Subject Specific Pedagogy (SSP) through its three core stages: identifying desired learning outcomes, designing appropriate assessments and tasks, and planning targeted learning activities. Respondents demonstrated increased competence in aligning instructional strategies with learning objectives through this framework. The results suggest that UbD provides a practical model for guiding teachers in curriculum-aligned material development. The structured approach helps educators better understand learning goals and translate them into classroom practice. UbD is an effective framework for improving PPG students’ mastery of Subject Specific Pedagogy. It is recommended that teacher training programs integrate UbD principles into their instructional models. Teachers are also encouraged to continuously refine their teaching strategies in line with evolving curriculum demands.